Optimal ratio of cash and non-cash payments - G. S. Panova (Vestnik MGIMO-Universiteta)
Analysis of the present condition and prospects of development of the monetary sector of the Russian economy. Quantitative parameters of aggregate turnover, including the value of cash and non-cash it. Researched issues restricting cash advance industry in Russia and other countries; the problems encountered by foreign States in imposing administrative limits on cash payments; provides specific recommendations and identified risks imposing such restrictions in Russia. The article deals with topical issues of optimization of structure of aggregate turnover. Analyzing the development of money turnover, the role and the place of cash in the economy, the author explored the basic approaches to the determination and regulation of money turnover, proposed a new approach to ensure transparency in money flows. Particularly promising cash flow optimization are: a) measures aimed at improving the cash turnover (including maintaining the stability of the national currency, improving the procedures for issuing and withdrawing money from circulation, determine the optimal structure of monetary aggregates, etc.) and b) development of cashless money turnover. The author's position is presented on the future of the scientific basis and practical realization of the optimal ratio of cash and cashless money turnover in Russia and other countries. In particular, felt the need to increase information transparency, openness international information exchange in order to improve monetary policy by countries at the national and international level. To develop common approaches (models) of the analysis and forecasting of financial markets, as well as the establishment of an international coordination centre responsible for the collection, verification and access to public information databases for the cross-country studies of banking and financial and monetary sphere.